Evaluation of Delaware Stars for Early Success Year 2 Report - Auger, Anamarie (RAND Corporation, 2015)
This report summarizes research activities conducted in the second year of Delaware's quality rating and improvement system for early learning and care programs. It features an analysis of state administrative data to assess provider participation rates in Delaware Stars and quality rating levels for participating providers, as well as a description of the financial incentives and technical assistance received by Delaware Stars providers.